Social Exchange Theory and Organizational Citizenship Behavior: Contemporary Perspectives in the Hotel Industry - Endri Haryati; Teguh Setiawan Wibowo (Westscience Press, 2026)
Introduction: The hotel industry is a service intensive sector where frontline employees simultaneously interact with supervisors, coworkers, and guests. Organizational Citizenship Behavior (OCB), defined as discretionary behaviors not formally rewarded, is critical for hotel success. Social Exchange Theory (SET) provides a framework for understanding OCB through reciprocal obligations, yet conceptual integration of Leader Member Exchange (LMX) and employee reciprocity in the hotel context remains limited. Methods: This conceptual paper synthesizes existing literature from Scopus indexed journals published between 1960 and 2025. A systematic search of databases including Scopus, Web of Science, and Google Scholar yielded 68 relevant articles comprising empirical studies, conceptual papers, and systematic reviews. Theoretical synthesis was employed to develop propositions and a conceptual model integrating SET, LMX, and employee reciprocity specifically for the hotel industry. Results: The synthesis reveals that OCB has evolved through five phases, with hotel research adopting three orientations: customer oriented, service oriented, and change oriented OCB. High quality LMX reduces employee envy and fosters thriving at work, enhancing service oriented and change oriented OCB, moderated by psychological empowerment and professional respect. Employee reciprocity emerges as a core mediating mechanism linking organizational, supervisory, and guest exchanges to OCB, including customer empowering behaviors and customer citizenship behaviors triggering reciprocal employee citizenship behaviors. Conclusion: SET remains a powerful framework for OCB in hotels when expanded to multiple exchange relationships. Future research should focus on longitudinal designs, cross cultural comparisons, technology impacts, and the dark side of OCB. Practical implications include building professional respect, psychological empowerment, and facilitating positive guest employee exchanges.